Anticancer Studies Of Ximenia Americana And Catharanthus Roseus In Human Breast Cancer Cell Lines Mcf7 And Mda-Mb-231 - Eltahir, Nagla Mustafa Eltayeb (2021)
Ximenia americana is a medicinal plant found in most African countries. It has been used traditionally to treat numerous diseases, including cancer. This study aimed to investigate the antiproliferative effect of X. americana leaves extract and fractions against breast cancer cell lines, determine the mechanisms of action and identify the major bioactive principle (s) in the most active fraction. Bioassay-guided fractionation of X. americana leaves using repeated open column chromatography and MTT assay resulted in the separation of SFr.6.2 as the most active subfraction with antiproliferative effect against MCF7 and MDA-MB-231 cell lines. SFr.6.2 showed dose- and time-dependent antiproliferative effect against both cell lines with more selectivity towards MCF7 cells. Moreover, the antiproliferative effect of SFr.6.2 on MCF7 was more significant than the standard drug tamoxifen. The IC50 values of SFr.6.2 and tamoxifen on MCF7 cells were 3.02 ± 0.21 and 5.97 ± 0.54 μg/ml, respectively. SFr.6.2 exerted less potency on non-tumourigenic cell line MCF 10A with a selectivity index of 3.14 compared to 1.64 for tamoxifen. Using flow cytometry analysis, SFr.6.2 showed dose-dependent cell cycle arrest at G2/M phase and apoptosis induction on MCF7 cells. SFr.6.2 chemical constituents were further analysed by LCMS-Q-TOF. The obtained chromatogram demonstrates the presence of valuable bioactive compounds which could be responsible for the anticancer activity of SFr.6.2. In addition to that, the chromatographic separation of X. americana leaves extract yielded three compounds, lupeol (1), daucosterol (2) and avicularin (3).